2015
DOI: 10.1016/j.bbrep.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ent-kaurenoic acid by ultra-performance liquid chromatography-tandem mass spectrometry

Abstract: ent-Kaurenoic acid (KA) is a key intermediate connected to a phytohormone gibberellin. To date, the general procedure for quantifying KA is by using traditional gas chromatography–mass spectrometry (GC–MS). In contrast, gibberellins, which are more hydrophilic than KA, can be easily quantified by liquid chromatography-tandem mass spectrometry (LC–MS/MS). In this study, we have established a new method to quantify KA by LC–MS/MS by taking advantage of a key feature of KA, namely the lack of fragmentation that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(19 reference statements)
1
9
1
Order By: Relevance
“…The LOD was determined by S/N ratio of 3 and found LOD was 1.3 pg. These results were lower than those from an early report 26 .…”
Section: Acontrasting
confidence: 81%
See 1 more Smart Citation
“…The LOD was determined by S/N ratio of 3 and found LOD was 1.3 pg. These results were lower than those from an early report 26 .…”
Section: Acontrasting
confidence: 81%
“…Therefore, we chose the MRM transition as 301.3 > 301.3. These unique characteristics were also observed by another study 26 . Different collision energies were tested on KA from 0 eV to 40 eV and there was no unique fragments observed.…”
Section: Asupporting
confidence: 78%
“…The recovery ratio of Ppcps/ks cell differentiation was set to 100% using 1 mM KA, and cell differentiation activities were detected in fractions 15 and 18 ( Figure 1B and Supplemental Figure 1C). Possible KA metabolites in these fractions were determined using liquid chromatographyelectrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS), as previously reported (Miyazaki et al, 2015). Considering KA (molecular weight 302) and the GA-catabolite GA 34 (molecular weight 348), negatively charged ions were monitored from m/z 299 > 299 to 350 > 350 ( Figure 1C), which revealed that fraction 18 contained unmetabolized KA with an m/z 301 > 301 [M À H]ion ( Figure 1C).…”
mentioning
confidence: 99%
“…1 Quantitative Analysis of Anthocyanin. The frozen plant tissues treated with or without compounds were homogenized, pretreated, and then applied to cation-exchange SPE (Oasis MCX) using the same procedure as described by Miyazaki et al 23 The SPE column was ■ RESULTS PAMD Inhibits the Growth of A. thaliana. PAMD was isolated from a chemical library of 9600 randomly synthesized compounds using SA-induced β-glucuronidase (GUS)-expressing plants (PR1::GUS line) and was determined to be an effective inhibitor of SA signaling.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%